Commercial scale invertebrate fisheries enhancement in Australia: Experiences, challenges and opportunities. (December 2015) - Hart, Anthony M.
Abstract: Stock enhancement or "assisted recruitment" for fisheries management in Australia is at an experimental R&D phase. Development of the science has focused largely on finfish targeted by the recreational sector; however it is considered that high value invertebrates will be the best candidates for commercial scale fisheries enhancement. Three main ingredients are required; technical capacity, governance capability, and the 'correct' species. The technical capacity needed is in the area of hatchery production and wild release methodologies, whilst the governance capability needed is informed policy that accounts for the complexities and interdisciplinary nature of stock enhancement. In particular, the appropriate articulation of policy to support economic development and integration into wild fisheries is currently lacking. If successful stock enhancement is implemented, the nature of fisheries management changes because the recruitment side of the fisheries equation is under substantial control, rather than just the production side. Management responses will require significant innovation, with a renewed emphasis on understanding the stock, rather than policing the fishers. By way of illustration, recent initiatives and key challenges encountered in Australian invertebrate fisheries are investigated through case studies. An example of a commercially-viable enhancement fishery that reflects solutions to the key challenges is also presented. The review ends with an argument to re-establish the context of stock enhancement in the discipline of ecological enhancement. This is a crucial and positive step forward for it recognises that, in principle, any renewable aquatic ecosystem has the potential to be enhanced instead of just depleted. Highlights: The challenges of integrating aquaculture and wild fisheries are identified and reviewed. Management responses will require significant innovation around conceptual principles. An integrated fishery and ecosystem enhancement model is presented. The model balances resource sustainability, sharing, conservation, and enhancement.